The Practice Of Sufism And Religious Moderation In The Kauman Pesantren Communities, Central Java, Indonesia - Bambang Irawan; Rosmaria Syafariah Widjajanti; Mohd. Syahiran Abdul Latif (UIN K.H. Abdurrahman Wahid Pekalongan, 2023)
This article deals with efforts to find solutions to the problems of extremism and religious radicalism. This was done by looking at the tolerant, peaceful, and harmonious practice of living together in the pesantren of Kauman and ethnic Chinese community Islamic boarding schools in Central Java, Indonesia. Data were obtained through interviews, observation, and documentation with qualitative methods. The founder of the pesantren instilled Sufistic values in the students. Sufistic values that are instilled include; mahabbah (love), tawazun (balance), tasamuh (tolerance), musawah (equality). The tasawuf doctrine applied by the pesantren of Kauman is very prospective and becomes a spiritual force in the present and the future. By implementing the Sufistic doctrines and religious moderation values, the threat of this disintegration and problems of extremism and religious radicalism that have been attempted by various groups can be totally removed, and hopefully, people would live in peace and harmony with plural, diverse and heterogenous ethnic.